SOCIAL AND ERGONOMIC EVALUATION OF MOTORCYCLE PROTECTIVE ISOLATION SHIELD FOR REDUCING COMMUNITY SPREAD OF COVID-19 - OLUKAYODE O. OYESIKU; OLASUNKANMI O. AKINYEMI; BASHIR O. ODUFUWA; BABATUNDE O. ADETIFA (Journal of Engineering Studies and Research)
Coronavirus (COVID-19) pandemic have rapidly evolved into a situation with profound effects on lifestyle and travel worldwide, ranging from a dramatic decrease in the patronage of formal public transport modes to an unprecedented increase in the usage of informal public transport modes. It is the main goal of this study to adapt a Motorcycle Protective Isolation Shield (MPIS) on a motorcycle for the reduction of community spread of COVID-19. MPIS was designed according to the anthropometry data obtained from motorcycle riders and passengers; and was fabricated using locally available materials. Anthropometry data used for the MPIS frame were sitting height (SH) and popliteal height (PH) of both motorcycle riders and passengers while seat depth (SD) of motorcycle riders and buttock knee length (BKL) of motorcycle passengers were used to locate the position of the MPIS mounted on the motorcycle. The 50% of the anthropometry data used for the design of MPIS is SH=800.00 mm, PH=500.00 mm, SD=300.00 mm and BKL=550.00 mm. The uncertainty modelling of motorcycle accident occurrence reveals the effect of higher speeds and the adapted MPIS during riding. The probability of occurrence of fatal crash, major crash and minor crash of motorcycle accident was 36.3%, 35.3% and 28.4%, respectively. The MPIS showed satisfactory post-riding assessment in terms of riding stability; riding, steering, and sitting convenience; and riding comfort for both the riders and passengers. It will be a good protection for motorcycle riders against the risk of COVID-19 and other air-borne infections.